Structure of the Capsid Size-Determining Scaffold of “Satellite” Bacteriophage P4 - James L. Kizziah; Cynthia M. Rodenburg; Terje Dokland (Viruses, 2020)
P4 is a mobile genetic element (MGE) that can exist as a plasmid or integrated into its Escherichia coli host genome, but becomes packaged into phage particles by a helper bacteriophage, such as P2. P4 is the original example of what we have termed “molecular piracy”, the process by which one MGE usurps the life cycle of another for its own propagation. The P2 helper provides most of the structural gene products for assembly of the P4 virion. However, when P4 is mobilized by P2, the resulting capsids are smaller than those normally formed by P2 alone. The P4-encoded protein responsible for this size change is called Sid, which forms an external scaffolding cage around the P4 procapsids. We have determined the high-resolution structure of P4 procapsids, allowing us to build an atomic model for Sid as well as the gpN capsid protein. Sixty copies of Sid form an intertwined dodecahedral cage around the T = 4 procapsid, making contact with only one out of the four symmetrically non-equivalent copies of gpN. Our structure provides a basis for understanding the sir mutants in gpN that prevent small capsid formation, as well as the nms “super-sid” mutations that counteract the effect of the sir mutations, and suggests a model for capsid size redirection by Sid.